1993
DOI: 10.1063/1.353169
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear piezoresistance effects in silicon

Abstract: Nonlinearity of the piezoresistance effects in p- and n-type silicon was measured at room temperature for three surface impurity concentrations and for three crystallographic orientations <100≳, <110≳, and <1̄1̄2≳. Piezoresistance coefficients up to third order in stress were obtained experimentally. Uniaxial stresses up to about 174 MPa were applied with currents flowing either parallel (longitudinal configuration) or perpendicular (transverse configuration) to them. A complete set of nin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
61
0
5

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(66 citation statements)
references
References 17 publications
0
61
0
5
Order By: Relevance
“…144,147 The piezoresistance coefficients depend on the impurity type and concentration. In conventional layout (Manhattan style), most transistors are built for h ¼ 45…”
Section: A Stress Effects In Bulk Simentioning
confidence: 99%
See 1 more Smart Citation
“…144,147 The piezoresistance coefficients depend on the impurity type and concentration. In conventional layout (Manhattan style), most transistors are built for h ¼ 45…”
Section: A Stress Effects In Bulk Simentioning
confidence: 99%
“…For the (001) Si-surface (which is prevalent in the microelectronics industry) and in-plane uniaxial stress, the 1st order piezoresistive tensor reduces to three independent piezoresistive coefficients (P 144,145 and the 2nd order piezoresistive tensor reduces to nine. 146,147 For low stresses ( 500 MPa), the higher-order terms are usually neglected. P (jh À uj ¼ 90 ) are the longitudinal and transverse piezoresistive coefficients.…”
Section: A Stress Effects In Bulk Simentioning
confidence: 99%
“…Piezoresistivity is only linear for small deformation, and prior work 16,17 has shown that a nonlinear deviation of 1% occurs at ξ pr = 139 MPa of stress in an ntype piezoresistor strained longitudinally. This nonlinearity implies a maximum force of…”
Section: A Piezoresistive Cantilevers Performancementioning
confidence: 99%
“…where l π and t π are the longitudinal and transverse coefficients respectively [16], β is the temperature coefficient of piezoresistance and is negative and is reported to be identical for both the coefficients [16] l σ and t σ are the longitudinal and transverse stresses respectively which are dependent on applied pressure and membrane dimensions [16]. β is typically of the order of -0.0032/ O C. The values of piezoresistive coefficients are taken from [17] for computing the changed value of resistance.…”
Section: Analytical Modelmentioning
confidence: 99%